Hak cipta dan perpustakaan - Ade Uswatun Sitorus (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
The library as an institution with an important role in disseminating information and knowledge, also have an important role in copyright. The activities carried out in a library is very closely related to publishing, preserving, memilihara and care as well as the creation of a work, but it also supports the efforts of libraries penegakaan copyrights and the prevention of copyright infringement